TEACHING ENGLISH VOCABULARY BY USING PICTURE WORD INDUCTIVE MODEL (PWIM) - Kamila, Andi Syifa; Supardi, Iwan; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was aimed at discovering the effect of Picture Word Inductive Model on studentsâ€™ vocabulary achievement on the seventh grade students of SMP Negeri 14 Pontianak in academic year 2016/2017. This research was a pre experimental research with one group pre-test post-test design. The research population was 212 students from 5 classes and by using cluster random sampling, the researcher chose class VII AÂ  that consisted of 35 students as the sample of the research. The data were gained from pre-test and post-test and analyzed by using t-test. The mean score of the pre-test was 58.14 which classified as â€œpoor to averageâ€ and the mean score of post-test was 77.86 which classified as â€œaverage to goodâ€. The finding showed that the t-test was 7.85. The t table with degree of freedom (df) 34 and significance level at 0.025 was 3.0019. Based on the data analysis above, the t-test was higher than the ttable (7.85 > 3.0019) which means that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Moreover, the effect size was 1.78, that result was more than 1.00 (ES > 1.00) which is categorized as strong effect. To sum up, the use of Picture Word Inductive Model in teaching vocabulary give a strong significant effect to improve studentsâ€™ vocabulary achievement.Â Keywords: Picture Word Inductive Model, Teaching Vocabulary, Vocabulary Achievement